THE CORRELATION BETWEEN STUDENTS’ HABIT IN WATCHING ENGLISH MOVIE AND VOCABULARY MASTERY AT THE SIXTH SEMESTER AT ENGLISH EDUCATION STUDY PROGRAM IN MUHAMMADIYAH UNIVERSITY OF METRO - Eva Faliyanti; Mira Arlin (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
The research objective of this research is to know whether there is any correlation between students’ habit in watching English movie and vocabulary mastery and the degree of correlation.The research design in this research is correlational study. It means that the researcher does not give any treatment to the students. There is no explanation before. The researcher only gives the test to the students. The researcher used cluster random sampling to get the sample. From the sample technique, the researcher got 39 students at the sixth semester at English education study program as the sample.Based on the research calculation by using correlation product moment, it is obtained that is 0,798, and is 0,320 in significant 5% and 0,413 in significant 1%. The average of students’ habit in watching English movie is 61. The average score of vocabulary mastery is 60,12. It shows that is higher than . It means that Ho is accepted and Ha is rejected The conclusion of this result shows that there is a positive correlation between students’ habit in watching English movie and vocabulary mastery at the sixth semester at English education study program in Muhammadiyah University of Metro Academic Year 2017/2018.